Taxonomic review of the grassland leafhopper genus Maiestas Distant (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) from Pakistan with description of a new species and two new records - Shah, Bismillah; Naveed, Hassan; Webb, Michael D.; Duan, Yani (Zootaxa, 2021)
The grassland leafhopper genus Maiestas Distant is reviewed from Pakistan with the description and illustrations of one new species, Maiestas sinuata Shah & Duan sp. n., and two new records, i.e., Maiestas maculata n. rec. and Maiestas trispinosa n. rec. A checklist of the known species of Maiestas from Pakistan is also given together with a key for their separation (males).